Harry Potter and the prisoner of Azkaban ravenclaw - Rowling, J.K (Bloomsbury Children's Books, 2019)
Let the magic of J.K. Rowling's classic Harry Potter series take you back to Hogwarts School of Witchcraft and Wizardry. Issued to mark the 20th anniversary of first publication of Harry Potter and the Prisoner of Azkaban, this irresistible Ravenclaw House Edition celebrates the noble character of the Hogwarts house famed for its wit, learning and wisdom. Harry's third year at Hogwarts is packed with thrilling Ravenclaw moments, including the appearance of the inimitable Professor Trelawney! With vibrant sprayed edges in Ravenclaw house livery, the book features beautiful house-themed cover artwork with intricate bronze foiling. With an exciting, bespoke introduction exploring the history of Ravenclaw House, and exclusive insights into the use of the Patronus Charm by favourite Ravenclaw characters, the book also boasts a spectacular image by Kate Greenaway winner Levi Pinfold of Cho Chang conjuring her Patronus. All seven books in the series will be issued in these highly collectable, beautifully crafted House Editions, designed to be treasured and read for years to come. A must-have for anyone who has ever imagined sitting under the Sorting Hat in the Great Hall at Hogwarts waiting to hear the words, ̀Better be RAVENCLAW!'.